Selectivity of hooks for seerfishes in the longline fishery of Thoothukudi coast, Tamil Nadu, India - Selva Muthu Kumaran, P.; Antony, Cheryl; Sundaramoorthy, B. (Indian Journal of Fisheries, 2015)
The study was conducted in Thoothukudi coast of Tamil Nadu to optimise the hook size for commercial exploitation of seerfishes. Analysis was done using three different sized hooks (Nos.7, 8 and 9). A wide range of length groups of seerfishes were caught by these hooks. The study concludes that hooks No. 7 and 8 are effective for commercial exploitation of seerfish.